Palestine Costume Archive Canberra, Australia - Allenby, Jeni, 1960-; Palestine Costume Archive (Canberra : Palestine Costume Archive; Jeni Allenby, 2002)
"The Palestine Costume Archive is a non profit research centre, established for safety in Canberra, Australia, in the early 1980s, and dedicated to the preservation and promotion of Palestinian and Middle Eastern costume and cultural heritage through long term research projects, a worldwide museum quality travelling exhibition program, publications and in depth educational and public programs. The Archive now holds a significant collection of Palestinian and Middle Eastern costumes and textiles, as well as several thousand publications of direct reference material." Web site contains information on and photographs of Palestinian dress and culture.
Title from title screen (viewed on 9 June 2004)
Text and graphics.
Mode of access: Internet via World Wide Web. Previously available at: http://www.palestinecostumearchive.org
Selected for archiving
Keywords: Clothing and dress -- Palestine; Costume -- Palestine; Palestinian Arabs -- Clothing; Women, Bedouin -- Palestine -- Clothing; Palestine -- Social life and customs